PERBEDAAN KADAR FLAVONOID TOTAL EKSTRAK DAUN SALAM (Syzygium polyanthum) DENGAN METODE REFLUKS DARI BEBERAPA JENIS PELARUT DAN AKTIVITAS ANTIBAKTERI - Yuliana Dewi Hastuti; Dewi Andini Kunti Mulangsri (Universitas Wahid Hasyim Semarang, 2021)
Bay leaves that it contains flavonoid compounds can inhibit the growth of Escherichia coli bacteria causes diarrhea. Hot extraction method can extract more compounds in the plants, particularly are heat stable. This study aimed to determine the different of total flavonoid content and antibacterial activity against Escherichia coli from bay leaves extracts that extracted with some solvent by reflux. The bay leaves extract was extracted with 70% ethanol, 96% ethanol, and methanol solvent. The spectrophotometric method was used to determine of total flavonoid contents at λmax 431,5 nm and operating time 30 minutes with AlCl₃ reagent. The disc diffusion method was used antibacterial activity test with chloramphenicol as a positive control and dimethyl sulfoxide as negative control. Analysis data of total flavonoid content with One Way Anova statistics, meanwhile the zone of inhibition from antibacterial activity test analysed by Two Way Anova continued with Tukey. The total flavonoid content of bay leaves extract (ethanol 70%, ethanol 96%, and methanol) were 6,089; 5,028; 4,052 mgQE/gram extract. There was significant difference of total flavonoid content between variation solvent and the most highest at 70% ethanol. Different extraction solvent and concentration serial of bay leaves extract showed significant difference and the most highest zone of inhibition at extract with 96% ethanol solvent.